A Case of Squamous Cell Carcinoma of Kidney Manifesting After Percutaneous Nephrolithotomy for Renal Pelvic Calculi - Hossain, Tohid Md Saiful; Kamal, Mohammed; Shafiquzzaman, Md; Mamun, Mamun Ur Rashid Al; Dhar, Shrabanti; Panjatan, Golam (Bangladesh Journal of Urology, 2023)
Squamous Cell Carcinoma (SCC) of the kidney is a rare neoplasm usually associated with long-standing nephrolithiasis. This disease has a poor outcome as it is highly aggressive and presents at an advanced stage. In this case report, we offer the SCC of the kidney in a middle-aged man who underwent Percutaneous Nephrolithotomy (PCNL) for long-standing renal stones. After a few days, there were recurrent episodes of pyelonephritis. After proper evaluation, renal mass was detected, and the patient underwent a radical nephrectomy. SCC was diagnosed from histopathology, and systemic therapy was started, but the patient died. So, the possibility of this rare neoplasm should be considered while treating long-standing nephrolithiasis. Bangladesh J. Urol. 2022; 25(1): 62-66